Applying Hadith Verification Method as A Critical Framework to Post-Truth and Hoax Phenomena on Social Media - Adam Nadzirul Wuqu'; Muktamat; Nasrulloh (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2026)
The post-truth era and the proliferation of hoaxes on social media exploiting religious texts have posed significant epistemological challenges within Muslim societies. The concept of Naqd al-Ḥadīṡ (Hadith criticism) has provided methodological inspiration as a framework for verifying the authenticity of information. Interestingly, there are indications of shared principles between information verification in the contemporary era and Naqd al-Ḥadīṡ, thereby enabling the methodological adoption within a critical literacy framework to counter digital disinformation. Arising from this reality, this study aims to examine two research problems: first, what are the methodological intersections between hadith verification methods and contemporary information verification? Second, how does the ISNAD-DIG model operate in verifying information that leads to religious narratives? Through a qualitative approach based on library research, reinforced by philosophical analysis grounded in coherence, correspondence, and pragmatism, the findings indicate that the principles of Naqd al-Ḥadīṡ—built upon Ittiṣāl al-sanad, Jarḥ wa ta‘dīl, matn criticism, Takhrīj, and authenticity assessment—align with the principles of Identify, Source Appraisal, Narrative Check, Authoritative Cross-Check, and Disposition in the ISNAD-DIG framework. Moreover, the implementational dimension of this model in the case of digital religious content demonstrates its effectiveness in identifying epistemic weaknesses, such as the absence of traceable sources, low credibility, and the lack of authoritative references. These findings affirm that Naqd al-Ḥadīṡ can be operationally adapted as a foundation for strengthening digital literacy and fostering a culture of critical thinking in the digital age.